Modelling a Fallschirmjäger Figure early Fallschirmjäger, 'Ready to jump' Operation Merkur, May 1941 : In 1/16 scale /: In 1/16 scale. (2012 copyright 2012) - Forns, Jaume Ortiz; Romero, Daniel Alfonsea
No abstract available